Employee Integrity to The Company During Work From Home (WFH) - Dyan Evita Santi; Puspaningrum (Future Science, 2022)
The purpose of this study is to describe the integrity of employees to the company during WFH. In a company, of course, the most influential resource is its human resources. The success of the company in carrying out its activities is influenced by the integrity of the company's employees. The author takes the object of the employees of PT Anugerah Pharmindo Lestari. Therefore, the author conducted a study to determine the integrity of employees towards the company during WFH. The method used by the author is a qualitative method, namely by interviewing informants to obtain the information needed in this study. The results and analysis obtained from this study as well as the conclusion obtained is that the integrity of employees employed at home during this pandemic has significantly decreased their integrity. Suggestions To make WFH more effective, you should do some tips, namely 1) Ensure a good internet connection, 2) Increase RAM capacity on the laptop, 3) get the best applications, 4) provide work reports on time.